Inducible Resistance to d-Cycloserine in Bacillus subtilis 168 - Clark, Virginia L. (1977)
Resistance to d-cycloserine could be induced in Bacillus subtilis 168 by sublethal concentrations of d-cycloserine. Sensitivity to the antibiotic could be regained by growth in the absence of d-cycloserine. The bactericidal activity of d-cycloserine apparently was not altered by resistant cells, and peptidoglycan synthesis was still inhibited by d-cycloserine in resistant cells. The d-cycloserine resistance apparently resulted from a decreased uptake of the antibiotic. The decrease in d-cycloserine transport could be prevented by simultaneous treatment of the cells with rifampin and d-cycloserine. d-Cycloserine was transported by the same system as glycine in B. subtilis. d-Cycloserine was able to exchange for intracellular glycine in both sensitive and resistant cells, suggesting that d-cycloserine is not excluded from the cell in resistant cultures.